VALUES CONTAINED IN SOMBAH TOR-TOR DANCE IN SIMALUNGUN COMMUNITY (NORTH SUMATERA) - Aryesha, Vinny (Jurnal Ilmiah Pendidikan Anak (JIPA), 2019)
The aim of this research is to eleborate and to look for the values which are contained in Tor-Tor Sombah Dance in Simalungun community (North Sumatera). The method that used in this research were qualitative and interpretative research method. The data were collected through observation, interviews, and documentation. The valid data technique uses data triangulation techniques. Furthermore, it is analyzed through interactive channels, namely data reduction, data presentation, and data verification. The results showed that the Sombah Tor-tor Dance has special values in displaying it, Togetherness Value, Brotherhood Value, and Social Value. Tor-tor Sombah dance is a traditional dance of the Simalungun people, born since the 13th century. Tor-tor Sombah dance consists of head movements, eye sight, hand movements, fingers and steps or stamping of feet. The Tor-tor Sombah dance is accompanied by traditional Batak musical instruments namely Gondrang, Mong-mongan, and Sarunei Bolon. Tor-tor Sombah dance is very safe to discuss with traditional ceremonies, namely rituals and entertainment events at the wedding party.Â Keywords: Values; Tor-Tor Sombah Dance